Balanced skills and the city: An analysis of the relationship between entrepreneurial skill balance, thickness and innovation - Elisabeth Bublitz; Michael Fritsch; Michael Wyrwich (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2013)
Being a jack-of-all-trades increases the probability of running an entrepreneurial venture successfully; but what happens to jack-of-few-trades who lack sufficient skills? This paper investigates a possible compensation mechanism between balanced skills and cities, and how this compensatory measure relates to performance. Specifically, we test and find support for the idea put forward by Helsley and Strange (2011) that high market thickness, such as that found in cities, can compensate for a lack of entrepreneurial skill balance. The results indicate that entrepreneurs with low skill balance benefit more from locating in cities than their counterparts with high skill balance. Innovative firms do not differ from other businesses in this respect.
Keywords: R1; L26; J24; O31; 330; agglomeration; balanced skills; entrepreneurship; thick markets; urban diversity